Trans Pacific Partnership (TPP) Dalam Bingkai Nawacita - Briando, Bobby (Badan kebijakan Fiskal, 2018)
The flow of international change is characterized by the growing strongness of the globalization trend in all lines including in the trade sector. This has an impact on the birth of international trade organizations. One such organization is Trans Pacific Partnership (TPP). TPP is a cross-national economic cooperation centered in the Asia Pacific region. The purpose of the study was to determine the impact if Indonesia joined the organization. This research uses SWOT analysis method. The result of the study recommends that Indonesia to review the desire to join in the organization's container. This is due to the contraindications to the values brought by the organization with the original values of Indonesia one of which is the spirit of NAWACITA. In addition, it is still necessary to more prepare supporting facilities and infrastructures in order to compete with other TPP organization members